Pengukuran kinerja dengan perspektif keuangan dan pelanggan pada CV. Kombos Manado 1 - Sahabati, Nathasya Claritha Edith; Alexander, Stanly W.; Lambey, Robert (Manajemen Bisnis dan Keuangan Korporat, 2024)
Performance measurement is not only viewed from a financial perspective, but can also be viewed from a non-financial perspective, such as the customer perspective. The financial and customer perspectives are related because a company cannot make a profit unless customers use its products or services. Performance is measured from a financial perspective to see whether the business strategy and its implementation have a significant impact on increasing the company's profits, while from a customer perspective it looks at how the company sells its goods or services to achieve better profits. The purpose of this research is to find out how the performance of CV Kombos Manado 1 is based on financial and customer perspectives. The research results show that the performance measurement from financial and customer perspective can be said to be good in terms of the company's ability to meet short-term obligations and to retain old customers and gain new customers.